Ability and Willingness to Pay Premium in the Framework of National Health Insurance System - Aulia Abdillah Ramadhan; Andri Reza Rahmadi; Henni Djuhaeni (Althea Medical Journal, 2015)
Background: The National Health Insurance is one of the government’s efforts to improve community access to health services. The government has fixed the premiums to be paid by community, except for underprivileged community. The aim of the study was to identify Ability to Pay (ATP) and Willingness to Pay (WTP) of the national health insurance premium.Methods: A descriptive study which involved 210  housewives who were chosen by rapid survey method was conducted from September to November 2013 in Cipacing village, Jatinangor, Sumedang, West Java. Data collection was using questionnaire to obtain level of ability and willingness to pay the health insurance premium. The results were compared to the required premium by the government (Rp 22,000,-).Results: Most of the respondents were only housewives, but there were still respondents who were private workers. Most of them were 20–39 years old. About 57.6% of the respondents were able to pay for the required premium, but Only 17.4% of the them were willing to pay according to the required premium.Conclusions: The ATP of the respondents are higher compared to the WTP, meaning that most of the respondents are able to pay the requires premium but are not willing to pay it. [AMJ.2015;2(4):502–5] DOI: 10.15850/amj.v2n4.635